English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

f(x) = 6 sqrt(x) + 1 ; g(x) = x^2 + 9

is it set up like this to solve?

6 sqrt(x^2+9) + 1 and (6 sqrt(x)+1)^2 + 9

2007-05-27 07:13:08 · 4 answers · asked by john d 2 in Science & Mathematics Mathematics

4 answers

the other way round
g*f = (6 sqrt(x)+1)^2 + 9
and f*g = 6 sqrt(x^2+9) + 1
for gf, you put f(x) for exery x that appears in g
for fg, you put g(x) for every x that appears in x.

2007-05-27 07:20:01 · answer #1 · answered by swd 6 · 0 0

Not quite. The functions you have are g∘f and f∘g, but in the wrong order. (g∘f)(x) = g(f(x)) = (6√x+1)²+9 and (f∘g)(x) = f(g(x)) = 6√(x²+9) + 1.

2007-05-27 14:20:01 · answer #2 · answered by Pascal 7 · 1 0

Yes, you seem like you understand the procedure.

2007-05-27 14:21:27 · answer #3 · answered by fcas80 7 · 0 1

it looks correct.... now simplify... ;)

2007-05-27 14:18:10 · answer #4 · answered by JAC 3 · 0 1

fedest.com, questions and answers